Analysis of the Influence of Media Context and Advertising Creativity on Consumer Attitudes in Brand Selection through the Effectiveness of Prepaid Sim Card Advertising - Prista Tarigan; Jeffry H. Sinaulan; Yoga Fortuna (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
Sell ​​phone industries have become more competitive, it helps the providers communicate their products and services more intensively. Consumers face many brand choices. This research aims to analyze the influence of advertising effectiveness which can improve the attitude toward the brand of prepaid Sim Card. The advertising effectiveness can be enhanced by selecting the appropriate media contexts and creative advertising. The research problem is to know how to improve the advertising effectiveness from the media context and creativity point of view that influences the attitude toward the brand. Based on this case, a theoretical model and six hypotheses were completed to be tested using the Structural Equation Model (SEM). The sample of this research is consumers of prepaid SimCard to wokers in the industrial area of ​​Cikarang, Bekasi Regency, West Java Province. From the result of this analysis, the Structural Equation Model has fulfilled the Gooness of Fix Index criteria; Chi Square 51.310 (< 53.38) GFI= 0.516 (>0.9) RMSEA =0.059 (<0.08) CFI =0.892 (limit margin from 0.95). CNIM/DF=1.350, Probability =0.073 >(0.05). The results show that the attitude toward the brand can be enhanced by improving the advertising effectiveness. Factors that affect the advertising effectiveness are media context and creativity. The theoretical implication from this research is that media context and influence creativity, advertising effectiveness and attitude toward the brand. Managerial implications suggest that brand choice, brand recognition, informative media context and original advertising are important factors to be considered